Monitoring and audit quality: Does quality standards compliance matter? - Richard Owusu-Afriyie; Dadson Awunyo-Vitor; Prince Gyimah; Kingsley Opoku Appiah (Cogent Business & Management, 2024)
Monitoring auditors through external inspections and assessments has become a significant driver of continuous improvement in the auditing profession. Surprisingly, there is a scarcity of research on how monitoring influences audit quality and the boundary conditions that may explain this relationship in developing countries. Therefore, this study develops and empirically tests a theoretical model that examines the relationship between monitoring and audit quality in the context of small and medium-sized practice firms (SMPs), using primary data collected from 209 SMPs in a developing country. The study employs variance-based structural equation modeling (SEM) using SmartPLS software to analyze the model's measurement and structural components. The findings reveal a statistically significant positive relationship between the monitoring of SMPs and audit quality, with quality standards compliance serving as a mediating variable that partially explains the mechanisms underlying this relationship. A key practical implication of the study is that audit partners should re-examine their firms' policies, procedures, audit methodologies, and processes to ensure adherence to legal, regulatory, and professional obligations or standards in order to achieve high-quality audits. This study contributes to the audit quality literature by providing novel empirical evidence, offering insights for academic research, informing policy decisions for governments and regulators, and providing practical implications for auditing professionals to enhance audit quality.
Keywords: 650; nternational standard on auditing (ISA); international standard of quality management (ISQM); audit monitoring; audit quality; mediation; small and medium practice (SMP) firms; auditing